Crosstalk Between Dermal Fibroblasts and Dendritic Cells During Dengue Virus Infection - Montes-Gómez, Alfredo E.; García-Cordero, Julio; Marcial-Juárez, Edith; Shrivastava, Gaurav; Visoso-Carvajal, Giovani; Juárez-Delgado, Francisco J.; Flores-Romo, Leopoldo; Sanchez-Torres, Ma. Carmen; Santos-Argumedo, Leopoldo; Bustos-Arriaga, José; Cedillo-Barrón, Leticia (Frontiers in Immunology, 2020)
Dengue virus infection (DENV-2) is transmitted by infected mosquitoes via the skin, where many cells from the dermis and epidermis are potentially susceptible to infected. Most of the cells in the infection area will establish an antiviral microenvironment to control viral replication. Although cumulative studies report permissive DENV-2 infection in dendritic cells, keratinocytes and fibroblasts, among other cells, little information is available regarding the crosstalk between them and their effect on the outcome of the infection. Therefore, our study focused on understanding the contribution of fibroblasts interacting with dendritic cells in the control or promotion of dengue. Our results suggest that dendritic cells promote an antiviral state over fibroblasts by enhancing the production of type I interferons. However, proinflammatory cytokines were not affected. Infected and non-infected fibroblasts promoted partial dendritic cell maturation, and the fibroblast-matured cells were less permissive to infection and showed enhanced type I interferon production. We also observed that the soluble mediators produced by non-infected or Poly (I:C) transfected fibroblasts induced allogenic T cell proliferation, but mediators produced by DENV-2 infected fibroblasts inhibited this phenomenon. The effect of fibroblast soluble mediators was analyzed on CD14+ monocytes to assess whether they affect monocyte derived dendritic cells (moDC) differentiation. Our data also showed that infected fibroblasts produced mediators that prevented differentiation of monocytes into dendritic cells, even in the presence of recombinant GM-CSF and IL-4. Cells with dendritic cell-like morphology appeared in the culture; however, flow cytometric analysis showed that they did not fully downregulate CD14 nor did they up-regulate CD1a. Our data revealed that fibroblast-dendritic cell crosstalk promoted an antiviral response mainly mediated by type I interferons over fibroblasts. Furthermore, the maturation of dendritic cells and T cell proliferation were promoted, which was inhibited by DENV-2-induced mediators.